Agronomic and anatomic performance of some soybean genotypes under optimal and water-deficit conditions - Soliman, Alaa A.; Mousa, Manar I.; Ibrahim, Mohamed A.; Baiumy, Khaled A.; Shaaban, Shimaa A.; Shabana, Mahmoud M. A.; Mohamed, Eman N. M.; Rehan, Medhat; Yu, Haitian; He, Yuhua (Frontiers in Plant Science, 2025)
Drought is a major environmental challenge that significantly limits crop productivity, and its impact varies based on the severity and timing of water scarcity. Soybean [Glycine max (L.) Merr.] faces considerable yield constraints under water-deficit conditions. This study evaluated the performance of eight soybean genotypes characterized by different levels of drought tolerance compared with the drought-tolerant world genotype PI416937 under normal [100% of crop evapotranspiration (ETc)] and deficit irrigation (60% ETc) conditions during the 2021 and 2022 seasons at Sakha Agricultural Research Station. Under deficit irrigation, the promising line H4L4 produced 92% (4.07 t/ha) of its productivity under normal irrigation, compared with 89% (2.12 t/ha) for the drought-tolerant genotype PI416937 in an average of two seasons. Applying deficit irrigation saved 37.54% and 38.61% of applied irrigation water across two seasons, whereas genotype H4L4 achieved the highest crop water use efficiency (0.95 and 0.90 kg seeds/m3) in the respective seasons, highlighting its potential for sustainable production under water-limited conditions. The promising line H4L4 also exhibited the highest stability and adaptability for seed yield across diverse environments, as confirmed by GGE biplot analysis. Furthermore, the drought susceptibility index (DSI) proved the superiority of H4L4 followed by PI416937, Giza 22, and DR101 for drought tolerance. Additionally, anatomic studies highlighted that PI416937 and H4L4 exhibited superior tolerance by maintaining thicker primary and secondary xylem tissues along with better stem and leaf integrity under irrigation levels. These resilient genotypes, thriving under water-deficit conditions, have significant potential as valuable genetic resources for breeding programs to enhance soybean productivity and sustainability. Additionally, H4L4 may be well-suited for widespread cultivation in water-deficit areas.